Temporal scales of variability in Regions Of Freshwater Influence on the French continental shelf over two decades - Martinez Almoyna, Maud; Charria, Guillaume; Sourisseau, Marc; Gaymard, Anne; Couvelard, Xavier; Theetten, Sébastien; Le Roux, Jean-François (Journal of marine systems, 2025)
The Regions Of Freshwater Influence (ROFIs) are defined as the area on the continental shelf in the vicinity of estuaries, where freshwater from the river significantly influence water properties and circulation. These regions are subject to a variety of dynamic forcings, including tides, winds and river runoffs, which exhibit considerable variability. The objective of this study is to identify the dominant time scales of variability of the three major ROFIs (Seine, Loire, and Gironde) of the French continental shelf and their evolution over the last two decades. In order to address these questions, we developed a high-resolution numerical simulation of the physical dynamics of the Bay of Biscay and the English Channel. The results demonstrate that the three ROFIs oscillate on the same two cycles: the semidiurnal cycle, caused by tides, and the annual cycle, linked to the seasonal variation in runoff. At the weekly and monthly time scales, two contrasting dynamics emerge. The Seine ROFI, situated in the eastern English Channel, is predominantly influenced by tides and exhibits a third oscillatory cycle, namely the fortnightly cycle. In the Bay of Biscay, the Loire and Gironde ROFIs are more influenced by wind events that shape their monthly variations. The interannual variations are primarily driven by runoff, with an observed reduction in ROFIs extension over the twenty years simulated correlated with a decrease in runoff. However, the combination of shorter timescale events impacts the interannual variability, leading to years with distinctive dynamics of the ROFIs. •French Regions Of Freshwater Influence (ROFI), complex temporal scale interactions.•Need of high resolution realistic numerical simulation to assess river impacts.•Interannual variability shaped by short timescale events.